2000
DOI: 10.1007/s002130000380
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine and valproate monotherapy: feasibility, relative safety and efficacy, and therapeutic drug monitoring in manic disorder

Abstract: The findings from this study suggest that both CBZ and VPA monotherapy is feasible for treatment of acute mania; however, VPA is more efficacious in terms of its early onset of action, lesser requirement for rescue medication and better tolerability. Further work needs to be undertaken to characterise the manic patients in terms of their differential psychopharmacologic response profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 26 publications
2
74
1
4
Order By: Relevance
“…Similar antimanic efficacy was observed for valproate in comparator trials with lithium (Freeman et al 1992;Bowden et al 1994Bowden et al , 2008 haloperidol (McElroy et al 1996a) and in one study against olanzapine (Zajecka et al 2002) but not in two others (Zajecka et al 2002;Tohen et al 2009b). Compared to carbamazepine (Vasudev et al 2000), valproate appeared superior in terms of overall outcome.…”
Section: Valproatementioning
confidence: 81%
See 2 more Smart Citations
“…Similar antimanic efficacy was observed for valproate in comparator trials with lithium (Freeman et al 1992;Bowden et al 1994Bowden et al , 2008 haloperidol (McElroy et al 1996a) and in one study against olanzapine (Zajecka et al 2002) but not in two others (Zajecka et al 2002;Tohen et al 2009b). Compared to carbamazepine (Vasudev et al 2000), valproate appeared superior in terms of overall outcome.…”
Section: Valproatementioning
confidence: 81%
“…Starting with the first studies of Okuma et al (1973), the efficacy of carbamazepine for the acute treatment of mania has been demonstrated in several small studies, both by Okuma's group and by other investigators (e.g., Ballenger and Post 1980;Mü ller and Stoll 1984;Emrich et al 1985;Post et al 1987). Comparative studies have been conducted with both typical neuroleptics, lithium and with valproate (Okuma et al 1979;Klein et al 1984;Placidi et al 1986;Stoll et al 1986;Lerer et al 1987;Lusznat et al 1988;Brown et al 1989;Okuma et al 1990;Small et al 1991;Vasudev et al 2000). The impression of these studies was that carbamazepine was overall equally effective as comparators, with a probably slightly slower onset of response compared to neuroleptics (Brown et al 1 A: Full evidence from controlled studies is based on: two or more double-blind, parallel-group, randomized controlled studies (RCTs) showing superiority to placebo (or in the case of psychotherapy studies, superiority to a ''psychological placebo'' in a study with adequate blinding) and one or more positive RCT showing superiority to or equivalent efficacy compared with established comparator treatment in a three-arm study with placebo control or in a well-powered non-inferiority trial (only required if such a standard treatment exists).…”
Section: Carbamazepinementioning
confidence: 99%
See 1 more Smart Citation
“…22,23 It has also been reported that the VPA-induced thrombocytopenia resolves without interruption of VPA treatment that means thrombocytopenia is transient and shows self-resolving phenomena (increase in platelet count) which may predict that there is some hidden mediator for that transient recovery from thrombocytopenia in some subjects during the course of the study. 24,25 So future researches should be required for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Estas três medicações demonstraram seu efeito terapêutico em estudos duplo-cego e com placebo (GOODWIN et al, 1969;BALLENGER e POST, 1980;POPE et al, 1991 (VASUDEV et al, 2000). Em relação ao lítio, alguns estudos mostram eficácia semelhante nas fases de mania e também com melhor tolerabilidade (BOWDEN et al, 1994), porém com resposta muito inferior nas fases depressivas agudas (STRAKOWSKI et al, 2000), mostrando melhor eficácia antidepressiva durante a fase de profilaxia em pacientes cicladores rápidos (CALABRESE et al, 1992).…”
Section: Tratamento Farmacológicounclassified